Optimization Manufacture of Virus- and Tumor-Specific T Cells - Natalia Lapteva; Juan F. Vera (Stem Cells International)
Although ex vivo expanded T cells are currently widely used in pre-clinical and clinical trials, the complexity of manufacture remains a major impediment for broader application. In this review we discuss current protocols for the ex vivo expansion of virus- and tumor-specific T cells and describe our experience in manufacture optimization using a gas-permeable static culture flask (G-Rex). This innovative device has revolutionized the manufacture process by allowing us to increase cell yields while decreasing the frequency of cell manipulation and in vitro culture time. It is now being used in good manufacturing practice (GMP) facilities for clinical cell production in our institution as well as many others in the US and worldwide.